2012
DOI: 10.1002/tea.21050
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between self‐efficacy and retention in introductory physics

Abstract: The quantitative results of Sources of Self‐Efficacy in Science Courses‐Physics (SOSESC‐P) are presented as a logistic regression predicting the passing of students in introductory Physics with Calculus I, overall as well as disaggregated by gender. Self‐efficacy as a theory to explain human behavior change [Bandura [1977] Psychological Review, 84(2), 191–215] has become a focus of education researchers. Zeldin and Pajares [Zeldin & Pajares [2000] American Educational Research Journal, 37(1), 215] and Zeldin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
169
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(184 citation statements)
references
References 84 publications
7
169
0
8
Order By: Relevance
“…Additionally, researchers have found that self-efficacy can predict achievement in science for high school students [24,25] and university students [8][9][10][11][12]. At Florida International University, an hispanic-serving institution in the southeastern United States, we have also found that a student's self-efficacy in physics at the beginning of an introductory physics course predicts the likelihood of a student passing that same course [26]. Further, in our reformed introductory physics classroom centered on Modeling Instruction, we find that students' physics self-efficacy is positively impacted after one semester of the course [20].…”
Section: Previous Research On the Development Of Self-efficacymentioning
confidence: 52%
See 2 more Smart Citations
“…Additionally, researchers have found that self-efficacy can predict achievement in science for high school students [24,25] and university students [8][9][10][11][12]. At Florida International University, an hispanic-serving institution in the southeastern United States, we have also found that a student's self-efficacy in physics at the beginning of an introductory physics course predicts the likelihood of a student passing that same course [26]. Further, in our reformed introductory physics classroom centered on Modeling Instruction, we find that students' physics self-efficacy is positively impacted after one semester of the course [20].…”
Section: Previous Research On the Development Of Self-efficacymentioning
confidence: 52%
“…Jessica and Lisa work together, checking that the proposed velocity-time graph is consistent with the horizontal line they have drawn for the acceleration-time graph (turns [18][19][20][21][22]. At the end of the episode we see Gina attempting to use the velocity information to find displacement using the area under the velocity-time graph (turns [26][27][28][29][30][31].…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Self-efficacy is the belief about one's capability to succeed on a particular task or in a specific situation. Research shows that apart from students' prior knowledge and skills, higher self-efficacy is positively correlated with expected grades in physics, enrollment in STEM courses, and career choices in STEM [6].…”
Section: Introductionmentioning
confidence: 99%
“…Males and females construct self-efficacy in science differently. Bandura's description of self-efficacy details the complexity of self-efficacy development (Sawtelle, Brewe, & Kramer, 2012).…”
Section: Science Identity and Perseverance In Sciencementioning
confidence: 99%